2008
DOI: 10.1002/pits.20318
|View full text |Cite
|
Sign up to set email alerts
|

Articles published in four school psychology journals from 2000 to 2005: An analysis of experimental/intervention research

Abstract: Using an experimenter-developed system, articles from four school psychology journals for the years 2000-2005 (n = 929) were classified. Results showed that 40% of the articles were narrative, 29% correlational, 16% descriptive, 8% causal-experimental, 4% causal-comparative, and 2% were meta-analytic. Further analysis of the causal-experimental studies suggested that both singlesubject and group designs were used to evaluate the effects of interventions delivered in schools (setting data) that improved student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
95
1
4

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(106 citation statements)
references
References 47 publications
6
95
1
4
Order By: Relevance
“…Unfortunately, this same study reported that across five main school psychology journals, intervention and prevention articles accounted for only 7.6 and 3.4% of the published articles, respectively. Follow-up studies of publication trends in education-based journals show nearly identical findings (e.g., Bliss et al 2008). With the need to prioritize reading intervention and prevention research in the U.S., this sheds light on the even greater dearth of intervention and prevention research with non-English-speaking students.…”
Section: Reading Fluency Intervention Research For Spanish-speaking Smentioning
confidence: 92%
“…Unfortunately, this same study reported that across five main school psychology journals, intervention and prevention articles accounted for only 7.6 and 3.4% of the published articles, respectively. Follow-up studies of publication trends in education-based journals show nearly identical findings (e.g., Bliss et al 2008). With the need to prioritize reading intervention and prevention research in the U.S., this sheds light on the even greater dearth of intervention and prevention research with non-English-speaking students.…”
Section: Reading Fluency Intervention Research For Spanish-speaking Smentioning
confidence: 92%
“…They found that only 1.45% of the articles in School Psychology Review were dedicated to interventions. Bliss, Skinner, Hautau, and Carroli (2008) examined articles in four school psychology journals between the years 2000 and 2005 (n = 929) and found that 8% were causal-experimental studies that evaluated interventions. They found that both single-subject designs and group designs were used to evaluate the effects of school-based interventions.…”
mentioning
confidence: 99%
“…This reflects a general trend in which school psychology journal publications are unlikely to present intervention research. For example, Bliss et al (2008) found that only 8.3 % of articles published in four school psychology journals from 2000 to 2005 represented causal-experimental research, and only 4.3 % were causal-comparative. A more recent content analysis of school psychology journal articles published from 2005 to 2009 indicated that only 12.7 % of articles represented intervention studies; 10.5 % were intervention studies with school-age youth (Villarreal et al 2013).…”
Section: Intervention Research In School Psychology Journalsmentioning
confidence: 98%